The effect of a professional cricket match schedule on selected immune parameters - Williams, AW; Myburgh, KH; Smith, C (South African Journal of Sports Medicine, 2004)
Objective. The impact of a professional cricket match schedule on white blood cell (WBC) distribution and lymphocyte activation (CD69 expression) was investigated. Methods. After a 3-month pre-season training period, physical and immune parameters were determined in 14 male cricketers before (B) and after (A) an intensive 5- week match schedule. Results. Exercise test results were unchanged from B to A. Total WBC counts were similar, but total lymphocyte and lymphocyte subpopulation counts decreased significantly. The CD4:CD8 ratio did not change. After in vitro stimulation, percentage CD4+CD69+ cells increased (B: 54.4 ± 9.7%, A: 64.0 ± 8.5%, p < 0.01), but absolute CD4+CD69+ cell counts did not change from B to A. In contrast, both the %CD8+CD69+ cells and absolute CD8+CD69+ cell count remained similar. Conclusion. A strenuous, interregional, professional cricket match schedule resulted in a decreased number of lymphocytes, but relatively increased in vitro reactivity of CD4+ cells, thus maintaining the absolute capacity of the CD4+ cells to become activated on stimulation. In cricketers who suffered upper respiratory tract symptoms during the match schedule (N = 7), none of the immune parameters investigated differed significantly from the others at B or A. SA Sports Medicine Vol.16(2) 2004: 22-27